Drug Delivery: Dendron‐Based Micelles for Topical Delivery of Endoxifen: A Potential Chemo‐Preventive Medicine for Breast Cancer (Adv. Funct. Mater. 17/2014). (May 2014) - Yang, Yang; Pearson, Ryan M.; Lee, Oukseub; Lee, Chan‐Woo; Chatterton, Robert T.; Khan, Seema A.; Hong, Seungpyo
<x xml:space="preserve">Abstract</x> Surface‐modified dendron micelles (DMs) are developed on page 2442 by Seungpyo Hong and colleagues as a potential platform for topical delivery of endoxifen (EDX). The data indicates that skin permeation of EDX is highly dependent on the surface group of the DMs. In particular, carboxylated DMs exhibit significantly enhanced permeation of EDX through both mouse and human skin layers, offering a potential alternative administration route for chemoprevention. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>